TAHIR MALIK’S "GOODBYE, CHILDHOOD!" THE ISSUE OF REBELLION AGAINST MENTAL ILLNESS IN THE STORY - F.A. Kurbanova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, writer Tahir Malik wrote in the detective genre "Goodbye, childhood!" the issue of spirituality raised in the story is discussed. The role of the writer in the development of this genre and his skills in image creation are revealed.